THE UTILIZATION OF THE WASTE OF CERAMIC SHERD AS SUBSTITUTE GRAVEL IN NORMAL CONCRETE TO COMPRESSIVE STRENGHT AND SPLIT TENSILE STRENGT OF CONCRETE - Lepie; Samuel Layang (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The purpose of this research is to determine the compressive strength and split tensile strength of concrete using the waste of ceramic sherd. Ceramic was used to replace gravel as coarse aggregate with percentage of 0%, 25%, 50%, 75% and 100%. This study was an experimental study using cylindrical test objects measuring 15 cm in diameter and 30 cm high. The total number of specimen are 50 pieces consisting of 30 test specimens for compressive strength testing and 20 specimens for testing the split tensile strength. Testing was done by using a Universal Testing Materials at the age of 14 days and 28 days.Based on the test results of compressive strength at 14 days old, the values obtained compressive strength of an average 8.77 MPa, 9.84 MPa, 10.27 MPa, 11.07 MPa, 12.07 respectively for the percentage of ceramic sherd 0%, 25%, 50%, 75% and 100%. Results of testing compressive strength at 28 days obtained the compressive strength average 12.47 MPa, 12.20 MPa, 8.67 MPa, 11.57 MPa, 12.00 respectively for the percentage of ceramic sherd 0%, 25%, 50%, 75% and 100%. Results of testing the split tensile strength at 14 days old values obtained for tensile strength an average of 4.80 MPa, 6.30 MPa, 4.75 MPa, 6.30 MPa, 6.15 respectively for the percentage of ceramic sherd 0%, 25%, 50%, 75% and 100%. Results of testing the split tensile strength at 28 days showed that the value of tensile strength an average 5:55 MPa, 6.50 MPa, 4.90 MPa, 6.35 MPa, 7.55 respectively for the percentage of ceramic sherd 0%, 25%, 50%, 75% and 100%